Watergate : the hidden history : Nixon, the Mafia, and the CIA - Waldron, Lamar, 1954- (Counterpoint : Distributed by Publishers Group West, 2012)
While Richard Nixon's culpability for Watergate has long been established, most recently by PBS in 2003, what is truly remarkable that after almost forty years, conventional accounts of the scandal still do not address Nixon's motive. Why was President Nixon willing to risk his reelection with so many repeated burglaries at the Watergate, and other Washington offices, in just a few weeks? What motivated Nixon to jeopardize his presidency by ordering the wide range of criminal operations that resulted in Watergate? What was Nixon so desperate to get at the Watergate, and how does it explain the deeper context surrounding his crimes? Through extensive investigative research, this book provides documented answers to all of those questions. It adds crucial missing pieces to the Watergate story, information that President Nixon wanted, but could not get, and that was not available to the Senate Watergate Committee or to journalists Woodward and Bernstein. This new information not only reveals remarkable insights into Nixon's motivation for Watergate, but also answers the two most important remaining questions: What were the Watergate burglars after? And why was Nixon willing to risk his Presidency to get it? This book reexamines the historical record, including new material only available in recent years. This includes thousands of recently declassified CIA and FBI files, newly released Nixon tapes, and exclusive interviews with those involved in the events surrounding Watergate, ranging from former Nixon officials to key aides for John and Robert Kennedy. This book also builds on decades of investigations by noted journalists and historians, as well as long overlooked investigative articles from publications like Time magazine, the Los Angeles Times, and the New York Times.